Data Privacy Protection in Islamic Communication Perspective - Saidah, Musfiah; Maylaffayza, Hilya (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Technology development brings many conveniences, but on the other hand, it also provides challenges, such as data security. The phenomenon of hacking personal data that ends in fraud and other crimes seems to be evidence. Technology in the era of society 5.0 was rising to facilitate human work, but it is used to misuse big data from the individual level. Social media provides opportunities for open privacy by revealing confidential personal data. In addition to requiring self-control, it also requires security and data protection. This research aims to analyze the phenomenon of data theft in the context of Islamic communication with solutions obtained from the perspective of the Qur'an. The method utilized is qualitative research through literature study using a constructivist paradigm. The results of this study revealed that internal and external factors caused data theft. The ability to filter information and information literacy in the digital space, maintain ethics in the media space, integrate roles between government and society, and protect digital communication from the perspective of the Qur'an have a positive effect on information preservation in the digital realm. In addition, continuous integration between the government and the community is also needed to overcome the rife data theft problem.